Challenges and Opportunities for Health Information Systems in Primary Care Clinics: A Mixed-Method Study among Health Workers in Manila, Philippines - Sucaldito, Ma Sergia Fatima; Malhotra, Rahul; Palileo-Villanueva, Lia; Besa, John Jefferson; Echague, Precious Angelica; Saquilayan, Mary John; Banzuela, Jessa Mae; Mendoza, Kian; Elepaño, Anton; Yan, Lijing L.; Østbye, Truls (Applied Clinical Informatics, 2025)
Globally, health information system (HIS) development projects face challenges regarding technology infrastructure, financing, user resistance, and interoperability. While these challenges are well-described in literature, most studies on HIS digitalization focus on the development of national and hospital HISs, with little focus on HISs in primary care. We described the HISs of two primary care clinics in Manila, Philippines in terms of data management procedures, governance, training and equipment, information culture, and health worker data skills, and investigated health workers' experiences during digitalization.This convergent mixed-methods descriptive study included two clinics: a nongovernmental organization (NGO)-operated clinic and a government-operated public health center (PHC). We surveyed eight health workers in the NGO clinic and six in PHC using the Performance of Routine Information System Management (PRISM) Community HIS evaluation tools from the World Health Organization and MEASURE Evaluation and conducted in-depth interviews among the same participants to explore their HIS experiences.Respondents in both clinics provided low scores on governance, indicating deficiencies in HIS strategy and documentation. PHC scored higher on data management, training, and equipment compared with the NGO clinic, whereas information culture scores were similar. Survey results reflected differences in IT infrastructure and services, stemming from PHC's larger size and funding. Interviews corroborated the survey results, highlighting barriers such as inadequate training and resources and the critical roles of internal communication and joint data stewardship, as described by the Filipino term “damayan,” which means working together in times of adversity. Additionally, interviews revealed expected benefits from digitalization, negative impact on workflow, and limited communication with external organizations.The findings highlight critical areas for enhancing HIS implementation and digitalization in primary care clinics in the Philippines. Addressing governance gaps, resource deficiencies, and communication barriers can improve HIS performance and help build digital resilience.
Keywords: health information systems; primary care; digitalization; health workers; Philippines